Realism and non-realism in Old Testament theology : a formal-logical and religious-philosophical assessment - Gericke, Jaco (Old Testament essays, 2006)
In contemporary Old Testament theology there is no consensus among its practitioners as to how we should perceive the relation between the intra-textual representations of YHWH and their supposed counterpart in extra-textual reality. In this paper, the author attempts to describe via both informal and formal-logical discourse, three major ontological positions operative in contemporary Old Testament theology as reconstructed from the perspective of philosophy of religion. It is suggested that the concepts of naïve-realism, critical realism and non-realism (or anti-realism) as utilised in this particular subdiscipline of philosophy may provide useful, nuanced and functional meta-ontological categories for classifying what Old Testament theologians appear to believe about the text-reality relation and the ontological status of YHWH.